FAKTOR - FAKTOR YANG MEMENGARUHI ADOPTION AND UTILIZATION OF E-GOVERNMENT: PERANAN INTENTION TO USE - Nabila Putri Husaini, (2023)
E-government is a commitment and government initiative to improve relations with the public and the business sector by improving the delivery of services, information and knowledge so as to save costs and efficiently by using information technology. The purpose of this study is to test and prove the effect of accessibility, complexity, usefulness, credibility, and simplicity on the intention to use e-government services through the intention to use e-government services as a mediating variable. The sample in this study were 795 Indonesian people who were obtained from distributing questionnaires. This study uses Structural Equation Modeling (SEM) with the help of the SmartPLS 3.0 application. The results of the study show that accessibility, complexity, usefulness and simplicity have a significant effect on the intention to use e-government services. Meanwhile, credibility has no influence on the intention to use e-government services. Then, the intention to use has a significant influence between the accessibility and simplicity variables on the adoption and utilization of e-government. Keywords: Accessibility, Complexity, Usefulness, Credibility, Simplicity, Intention to Use e-government services, Adoption and Utilization of E-Government.